Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan: The Influence of Financial Literacy and Lifestyle on Financial Management Behavior - Siruang, Kefin; Posi, sahrul hi; Kaiyeli, Nasrullah (Universitas Bojonegoro, 2024)
Financial literacy is a person's ability to manage finances as well as possible. Lifestyle is a need related to a person's desire for something he wants to fulfill his pleasure by changing their lifestyle. This study aims to determine the effect of financial literacy and lifestyle on financial management behavior of accounting and business administration students at Hein Namotemo University. Data was collected by means of a survey using a questionnaire given to 41 respondents. The data analysis technique used classical assumption test, multiple linear regression, t test, F test, and coefficient of determination. The results of this study indicate that the financial literacy variable has a positive and significant effect on student financial management behavior. While the lifestyle variable has a positive but not significant effect on student financial management.